Real-world Data Reveal Long Drug Survival for Guselkumab in Patients with Plaque Psoriasis - Marloes E. van Muijen; Sarah E. Thomas; Douwe Vellinga; Silke Bouwman; Martijn B.A. van Doorn; Klaziena Politiek; Marisol E. Otero; Juul M.P.A. van den Reek; Elke M.G.J. de Jong (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)